Influence Of Work Motivation And Work Environment For Employee Performance By Job Satisfaction As An Intervening Variable Of Investment And One Stop Services (DPM-PTSP) In Makassar - Ade Wijaya Muslim; Muh Idrus Taba; Maat Pono (Jurnal Mirai Management, 2023)
This research is focusing to understanding the influence of motivation and environment at work for employee performance with satisfaction of job as intervening variable on one-stop investment and integrated services in Makassar. Primary data is used in this research while conduct observation, personal interview along with questionnaire perform to collect the data. Samples in this study were all employees of DPM-PTSP Makassar City, and used a propably sampling technique with simple random sampling so that the number of samples used was 100 people from 160 observation data. In this study, the determination of the number of samples used the Slovin formula with a precision of 5%, the data management used was SMARTPLS Software. The result shown that motivation and environment at work both of them have significant with positive contribution for satisfaction on job, while motivation have positive along with significant influence for the performance of employee, it goes different with work environment that shown positive insignificant impact for employee performance. Satisfaction in job shown positive along with significant influence for performance of employee, while work motivation result shown significant but indirect influence for the employee performance by job satisfaction. The environment if work shown significant but indirect influence for the performance of employee by the job satisfaction. Keywords: Work motivation, Work environment, Employee Performance, Job Satisfaction.